Value of Certifications when Seeking Construction Employment. Issue 1 (2nd January 2020) - Barrows, Matthew; Clevenger, Caroline M.; Abdallah, Moatassem; Wu, Wei
ABSTRACT: Construction graduates and professionals have many professional-development and educational options available. This study explores a range of certifications and evaluates their value to individuals seeking advertised construction management employment. The study analyzed 300 job postings for three US regions across construction industry sectors and job levels. Results indicate that employers prefer applicants to have certification(s) 16% of the time, with increasing preference at the more senior levels. Project Management Professional (PMP), Leadership in Energy and Environmental Design Accredited Professional (LEED AP), and Occupational Safety and Health Administration (OSHA) credentials were the most frequently requested, with OSHA being most preferred at the junior level. Contributions of this research include (1) identification of observable and statistically significant trends for certifications on construction job postings and (2) development of a method to assess the relative value of various certifications. While findings quantifying value may or may not be generalizable, they demonstrate a method for comparison, as well as confirm that certifications, to a limited extent, are a differentiator in the construction hiring process, particularly at more senior levels. Findings are beneficial for recent graduates and current professionals seeking career advancement, and also inform training and academic programs striving to provide construction career-specific competencies.